ANALISIS PERBEDAAN PENDAPATAN PETANI KARET DENGAN SISTEM LELANG DAN NON LELANG DI DESA CIPTA PRAJA KECAMATAN KELUANG KABUPATEN MUSI BANYUASIN - Armedi, Cacak; Kurniawan, Rahmat (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2020)
ABSTRACT This study aims determine To find out the differences in income of rubber farmers with the auction and non auction system in Cipta Praja Village, Keluang Subdistrict, Musi Banyuasin District.    This research was conducted in Cipta Praja Village, Keluang Subdistrict, Musi Banyuasin Regency from June to August 2019.  The research method  used was  a survey.  Sampling methods,  namely the first  is  purposive sampling (Disproportionate Stratified Random Sampling (unbalanced random), where this study amounted to 30 people from the auction and non-auction systems used as samples  Data collection methods used in this study were observation and interviews directly to respondents who have been determined, in addition to the type of data collected are primary data and secondary data. Furthermore, analysis in this research Data collection methods used in this study were observation and interviews directly to respondents who have been determined, in addition to the type of data collected are primary data and secondary data. Furthermore, analysis data  in this research are descriptive analysis and quantitative descriptive, then to calculate the outflow of labor and labor income using the formula. Based on the results of the study that the difference between the income of rubber farmers with the auction and non- auction  systems  in  Cipta  Praja  Village,  Keluang  District,  Musi  Banyuasin Regency,  for  which  the  auction  system  averages  Rp  1,435,135.67  haktar  per month and for non-auction Rp 1,104,248.14 hectares per monthABSTRAK Penelitian ini bertujuan untuk mengetahui Untuk mengetahui perbedaan pendapatan petani karet dengan sistem lelang dan non lelang di Desa Cipta Praja Kecamatan Keluang Kabupaten Musi Banyuasin. Penelitian ini dilaksanakan di Desa Cipta Praja Kecamatan Keluang Kabupaten Musi Banyuasin pada bulan Juni sampai dengan bulan Agustus 2019. Metode penelitian yang digunakan adalah survei. Metode penarikan contoh, yaitu yang pertama adalah purposive sampling (sengaja) dan Disproportionate Stratified Random  Sampling  (acak  tak  berimbang),  dimana  penelitian  ini  berjumlah  30 orang dari sistem lelang dan non lelang yang dijadikan sampel. Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi dan wawancara langsung kepada responden yang telah ditentukan, selain itu jenis data yang dikumpulkan yaitu data primer dan data sekunder. Selanjutnya analisis data dalam penellitian ini analisis deskriptif kualitatif dan deskriptif kuantitatif, selanjutnya untuk menghitung curahan tenaga kerja dan pendapatan tenaga kerja menggunakan rumus. Berdasarkan hasil penelitian bahwa perbedaan pendapatan petani karet dengan sistem lelang dan non lelang di Desa Cipta Praja Kecamatan Keluang Kabupaten Musi Banyuasin untuk yang sistem lelang rata-rata Rp 1.435.135,67 haktar per bulan dan untuk non lelang Rp 1.104.248,14 hektar per bulan